Characterization of GPS and EGNOS amplitude scintillations over the African equatorial/low-latitude region. Issue 9 (1st May 2019) - Akala, A.O.; Oyeyemi, E.O.; Arowolo, O.A.; Doherty, P.H.
Abstract: This study characterizes GPS and EGNOS amplitude scintillations over the African equatorial/low-latitude region. The data set covers January–December 2013 at three stations; namely, Cape-Verde Island (Lat: 16°N, Lon: 24°W, Mag. Lat: 11°N), Dakar (Lat: 14.75°N, Lon: 17.45°W, Mag. Lat: 5.88°N) [Senegal] and Addis Ababa (Lat: 9.03°N, Lon: 38.77°W, Mag. Lat: 0.18°N) [Ethiopia]. Firstly, we investigated the seasonal variations of scintillations over the study sites. In doing this, we suppressed multipath effects on the data by imposing a 30° elevation masking on the data. Seasonally, scintillations recorded highest occurrences during equinoxes, and the least during June solstice. Secondly, we investigated scintillation occurrences at the three sites on a satellite-by-satellite basis at varying elevation and azimuthal angles. Generally, scintillations (at both low- and high-elevation angles) recorded the highest occurrences at Cape-Verde, followed by Dakar, and the least at Addis Ababa. Scintillation activities were generally localized within the northern skies of the study locations. EGNOS satellites signals scintillated at Dakar and Addis Ababa during the time intervals when GPS satellites signals experienced scintillations. Data showed that Cape-Verde is off the EGNOS geostationary satellite footprint. These results have the potentials of supporting the development of scintillation models for equatorial Africa. Furthermore, with a view to providing robust services for the African user community, the current research effort is also expected to provide value addition to GPS and EGNOS service providers and system designers.